Practice budgets and the patient mix of physicians - Evaluating the effects of remuneration system reforms on physician behaviour in Germany - Hendrik Schmitz (Verein für Socialpolitik, 2010)
We analyse the effect of a change in the remuneration system for physicians on the lengths of treatments of patients as measured by the number of doctor visits using data from the German Socio-Economic Panel over the period 1988- 2003. In particular, we analyse the introduction of a fixed budget for the ambulatory sector in 1993 and the introduction of individual practice budgets in 1997 for the publicly insured. With a random-effects-type two-part model, we find evidence that the reforms did not change the patients' behaviour (and access to health care) but that the introduction of individual practice budgets in 1997 reduced the treatment durations of the publicly insured. At the same time, treatment durations increased for the privately insured. This can be seen as evidence that physicians respond to the change in incentives induced by the reform.
Keywords: I11; I18; C23; 330; supplier-induced demand; latent class hurdle model; ambulatory care; practice budgets